2020
DOI: 10.1101/2020.01.10.901736
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The synthetically produced predator odor 2,5-dihydro-2,4,5-trimethylthiazoline increases alcohol self-administration and alters basolateral amygdala response to alcohol in rats

Abstract: Post-traumatic stress disorder (PTSD) is a psychiatric illness that can increase the risk for developing an alcohol use disorder (AUD). While clinical data has been useful in identifying similarities in the neurobiological bases of these disorders, preclinical models are essential for understanding the mechanism(s) by which PTSD increases the risk of developing AUD. The purpose of these studies was to examine if exposure of male Long-Evans rats to the synthetically produced predator odor 2,5-dihydro-2,4,5trime… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Since we chose to not use another cohort of surgerized/transgenic mice for testing in the EPM, it is important to note that testing without prior TMT exposure was a limitation. TMT can have mixed effects on time spent in the open arms of the EPM, which can be dependent on the TMT concentration ( Hacquemand et al, 2013 ; McGregor et al, 2002 ; Makhijani et al, 2020 ). This points to the EPM as a distinct, novelty-related probe, which may not be robust to differentiate EtOH-related phenotypes after a confounding TMT exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Since we chose to not use another cohort of surgerized/transgenic mice for testing in the EPM, it is important to note that testing without prior TMT exposure was a limitation. TMT can have mixed effects on time spent in the open arms of the EPM, which can be dependent on the TMT concentration ( Hacquemand et al, 2013 ; McGregor et al, 2002 ; Makhijani et al, 2020 ). This points to the EPM as a distinct, novelty-related probe, which may not be robust to differentiate EtOH-related phenotypes after a confounding TMT exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have used exposure to the scent of a predator as a stressor that produces lasting behavioral consequences with relevance to stress-related neuropsychiatric disorders [42][43][44][45][46][47][48][49][50][51][52][53][54][55]. For example, exposure to the synthetically derived fox odor 2,5 dihydro 2,4,5 trimethylthiazoline (TMT) produces avoidance and freezing behaviors, indicative of a fear like response and increased serum corticosterone, reflecting a stress response [47,50,56,57]. Other studies have showed lasting anxiety like and hyperarousal behavior, as well as avoidance of a TMT paired context or cue [43,51].…”
Section: Introductionmentioning
confidence: 99%